Dopamine, religiosity, and utilitarian moral judgment. (2nd November 2021) - Mueller, Dana; Halfmann, Kameko
ABSTRACT: Our goal was to examine the relationship between biological and sociocultural factors that predict utilitarian moral judgment. Utilitarian moral judgments occur when a specific action is based on the outcome rather than its consistency with social norms. We predicted that (1) individuals with higher levels of dopamine will make more utilitarian decisions and (2) individuals who express greater religiosity will make less utilitarian judgments. We measured dopamine using spontaneous eyeblink rate, an indirect measure associated with striatal dopaminergic transmission. A total of 96 participants completed a utilitarian moral judgment task where they made judgments regarding nonmoral, impersonal, personal low-conflict, and personal high-conflict moral dilemmas. Then, participants completed a questionnaire measuring religiosity. We found a negative relationship between religiosity and the proportion of "yes" judgments participants made in the high-conflict personal dilemmas, which was consistent with our second hypothesis. None of our other hypotheses were supported. Understanding biological and cultural factors that relate to utilitarian moral judgment may also help in developing artificial intelligence that more closely mimic human behavior.